Risk Factors for Cytomegalovirus Reactivation and Association With Outcomes in Critically Ill Adults With Sepsis: A Pooled Analysis of Prospective Studies. (7th November 2020) - Imlay, Hannah; Dasgupta, Sayan; Boeckh, Michael; Stapleton, Renee D; Rubenfeld, Gordon D; Chen, Ying; Limaye, Ajit P
Abstract: We performed multivariable analysis of potential risk factors (including cytomegalovirus [CMV] reactivation) for clinical outcomes by day 28 (death or continued hospitalization, ventilator-free days, intensive care unit (ICU)-free days, hospital-free days) from pooled cohorts of 2 previous prospective studies of CMV-seropositive adults with sepsis. CMV reactivation at any level, >100 IU/mL, >1000 IU/mL, peak viral load, and area under the curve were independently associated with the clinical outcomes. We identified the potential effect size of CMV on outcomes that could be used as end points for future interventional trials of CMV prevention using antiviral prophylaxis in ICU patients with sepsis.